Exploring nitrogen-mediated effects on Fe and Cu cluster development in graphene: a DFT study - Alvarado-Leal, L. A; Paez-Ornelas, J. I; Ruiz-Robles, M. A; Guerrero-Sánchez, J; Romo-Herrera, J. M; Fernández-Escamilla, H. N; Takeuchi, Noboru; Perez-Tijerina, E. G (Nanoscale, 2024)
The controlled growth and stability of transition metal clusters on N-doped materials have become the subject of intense investigation for unveiling comprehension on the cluster growth evolution. In this study, we investigated the growth mechanisms of non-magnetic (copper) and magnetic (iron) clusters on graphene with two atomic vacancies, with and without pyridinic nitrogen (N). Our results determine the role of pyridinic N in the growth and physicochemical properties of the mentioned metal clusters. In an N environment, Cu grows perpendicularly, whereas under N-deficient conditions, the clusters agglomerate. Fe cumulate-type clusters are formed regardless of the presence of N. However, N causes the Fe clusters to rise over one side of the surface without deforming the monolayer; meanwhile, in the absence of N, the Fe clusters protrude from both sides of the monolayer. Remarkably, the presence of N makes it feasible to induce magnetization in the Cu n -N 4 V 2 systems and aid in focalizing the magnetic properties on the Fe clusters for the Fe n -N 4 V 2 case. These findings offer insights into the role of N in cluster growth, with potential implications for diverse applications, including magnetic and electrocatalytic materials. The controlled growth and stability of transition metal clusters on N-doped materials have become the subject of intense investigation for unveiling comprehension on the cluster growth evolution.